Ortner's syndrome caused by dissecting aortic aneurysm - Ferhat Özyurtlu; Halit Acet; Mehmet Zihni Bilik; Abdurrahman Tasal (KARE Publishing, 2013)
Ortner's syndrome results in hoarseness caused by compression of the left laryngeal recurrent as a result of cardiovascular pathology. A wide range of cardiovascular such as valvular heart disease, thoracic aortic aneurysm and congenital heart disease may result in Ortner's syndrome. We present a case of Ortner's syndrome caused by a large diameter (120 mm) aneurysm, previously unreported in the literature. A male patient aged 71 years was admitted to our clinic for exertional dyspnea, asthenia and hoarseness. In the indirect laryngoscopic examination, left vocal cord paralysis of the patient was observed and his chest X-ray revealed a mass with a diameter of 120 mm that filled the left upper zone. A dissected aortic aneurysm 120 mm in diameter in arcus level at thorax was seen in CT imaging. Surgical treatment was suggested; however, the patient refused treatment and died at the 4th month of the follow up period.